2017
DOI: 10.1016/j.stem.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Terminally Committed Hepatocytes to Culturable Bipotent Progenitor Cells with Regenerative Capacity

Abstract: A challenge for advancing approaches to liver regeneration is loss of functional differentiation capacity when hepatocyte progenitors are maintained in culture. Recent lineage-tracing studies have shown that mature hepatocytes (MHs) convert to an immature state during chronic liver injury, and we investigated whether this conversion could be recapitulated in vitro and whether such converted cells could represent a source of expandable hepatocytes. We report that a cocktail of small molecules, Y-27632, A-83-01,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
241
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(275 citation statements)
references
References 34 publications
28
241
5
1
Order By: Relevance
“…9G). A recent study has shown the conversion of terminally differentiated hepatocytes to bipotent AFP‐positive HPCs with regenerative capacity by adding a chemical cocktail to the culture media 42. It is therefore possible that the AFP‐expressing immature hepatocytes observed in the present study acquire the ability to differentiate into both hepatocytes and cholangiocytes in certain experimental conditions.…”
Section: Discussionmentioning
confidence: 73%
“…9G). A recent study has shown the conversion of terminally differentiated hepatocytes to bipotent AFP‐positive HPCs with regenerative capacity by adding a chemical cocktail to the culture media 42. It is therefore possible that the AFP‐expressing immature hepatocytes observed in the present study acquire the ability to differentiate into both hepatocytes and cholangiocytes in certain experimental conditions.…”
Section: Discussionmentioning
confidence: 73%
“…If similar protocols could be established using human hepatocytes, this offers an additional source for HLCs for use in HT. Furthermore, the bipotent properties of CLiPs suggest that they could be used to tackle diseases related to the biliary tree as well as the liver [68]. …”
Section: Alternative Cell Sources For Hepatocyte Transplantationmentioning
confidence: 99%
“…Conditions have recently been described to achieve long-term culture of bi-potent liver progenitor cells acquired from liver tissue, which form organoids that are genetically-stable in vitro and appropriately express biliary markers [45]. Even more recently, a cocktail of small molecules has been published that have the potential to convert mature hepatocytes into bipotent chemically-induced liver progenitor cells with the capacity to differentiate into both mature hepatocytes and biliary epithelial cells [46]. Indeed, Katsuda et.…”
Section: Functional Modeling Of Alagille Syndromementioning
confidence: 99%
“…al . were able to show that these cells are able to repopulate chronically-injured liver tissue [46]. Thus far, these experiments have been done only in rat and mouse, and it remains to be seen whether human hepatocytes are chemically-susceptible to this conversion.…”
Section: Functional Modeling Of Alagille Syndromementioning
confidence: 99%